2019
DOI: 10.1111/and.13286
|View full text |Cite
|
Sign up to set email alerts
|

Early varicocelectomy by percutaneous scleroembolization improves seminiferous tubules spermatozoa release in the adolescent phase of testicular growth

Abstract: Varicocele is a rather common andrological condition in adolescents, which can adversely affect testicular growth and seminal parameters, leading to infertility in about 20% of adults. The aim of this study was to investigate if treating varicocele before the age of 18 is a beneficial option to improve testicular hypotrophy and seminal parameters and if minimally invasive techniques could be an appropriate treatment choice for adolescent varicocele associated with spermatic vein reflux. A percutaneous scleroem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
3
8
2
Order By: Relevance
“… 26 On the contrary, the patient's age seems not to be related with the post‐surgery seminal improvement. This result is in contrast with other reports 41 , 42 but, probably, in our setting the duration of varicocele is a more a relevant parameter than age at surgery. Taken together, these results could help the clinician in the current clinical approach to varicocele‐related male infertility.…”
Section: Discussioncontrasting
confidence: 99%
“… 26 On the contrary, the patient's age seems not to be related with the post‐surgery seminal improvement. This result is in contrast with other reports 41 , 42 but, probably, in our setting the duration of varicocele is a more a relevant parameter than age at surgery. Taken together, these results could help the clinician in the current clinical approach to varicocele‐related male infertility.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, the patient's age seems not to be related with the post-surgery seminal improvement. This result is in contrast with other reports 38,39 but, probably, in our setting the duration of varicocele is a more a relevant parameter than age at surgery. In our cohort, seminal improvement is detected only in patients treated with sub-inguinal ebectomy.…”
Section: Discussioncontrasting
confidence: 99%
“…We also evaluated whether age was associated with postoperative seminal recovery determined a significant increase in sperm parameters in patients aged ≤30 years compared with those aged >30 years. This result contradicts the findings reported by Morini et al but it is consistent with other reports [24–26] …”
Section: Discussionsupporting
confidence: 78%
“…This result contradicts the findings reported by Morini et al but it is consistent with other reports. [24][25][26] In our study, all 4 factors evaluated in semen analysis showed significant improvement after varicocelectomy. Similarly, in a study by Al Bakri et al, [27] the mean sperm count significantly increased at 3 to 6 months after varicocelectomy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation